Green Action by Front Office Staff in Increasing Environmental Concern at the Sofitel Bali Nusa Dua Hotel - Dani Gunawan; Ni Made Ary Widiastini; Ni Luh Putu Triyanti Aristiana Dewi (International Journal of Green Tourism Research and Applications, 2024)
The hotel industry is increasingly under pressure to implement sustainable practices due to environmental concerns. This research explores the implementation of environmentally friendly actions carried out by front office staff at the Sofitel Bali Nusa Dua Hotel, which aims to increase environmental awareness among guests and employees. Using descriptive qualitative research methods, data was collected through interviews, observation and document analysis. These findings reveal a significant commitment to sustainability in front office operations, reflected in waste reduction, energy efficiency and guest engagement in environmentally friendly practices.  This research shows that the hotel's commitment to sustainability has fostered a culture of environmental awareness, leading to positive behavioral changes and increased guest satisfaction. The integration of environmentally friendly practices into hotel operations and the active participation of staff and guests in these initiatives have proven instrumental in advancing the hotel's sustainability agenda. This study contributes to understanding the practical application of environmental sustainability in the hospitality industry, highlighting the important role of front office staff in promoting environmentally friendly initiatives.